The Effectiveness of Mindfulness-Based Stress Reduction on Emotion Regulation, Pain Self-Efficacy, and Pain Perception in Patients with Cardiovascular Diseases - Pourrostam, Mahdieh; Khosravi Hampa, Ali Akbar; Ganjali, Zeinab (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective: Stress is recognized as one of the main factors affecting cardiovascular diseases. Mindfulness-Based Stress Reduction (MBSR) has gained attention as an innovative approach to improving the psychological state of patients. This study aimed to investigate the effectiveness of MBSR on emotion regulation, pain self-efficacy, and pain perception in patients with cardiovascular diseases.Methods and Materials: This experimental study was designed with a control group and an experimental group. Sixty patients with cardiovascular diseases were randomly divided into two equal groups. The experimental group underwent the MBSR program for 8 weeks, while the control group received no intervention. The instruments used included the Emotion Regulation Questionnaire (ERQ), the Pain Self-Efficacy Questionnaire (PSEQ), and the Pain Perception Questionnaire (PPQ). Data were analyzed using appropriate statistical tests.Findings: The results indicated that MBSR significantly improved emotion regulation and increased pain self-efficacy in the experimental group compared to the control group (p< 0.05). Additionally, pain perception in the experimental group significantly decreased (p< 0.05).Conclusion: The findings of this study suggest that MBSR can be used as an effective method in reducing stress and improving emotion regulation, pain self-efficacy, and pain perception in patients with cardiovascular diseases. It is recommended that this method be included as part of the therapeutic and rehabilitation programs for these patients.